Nγ-hydroxyasparagine: a multifunctional unnatural amino acid that is a good P1 substrate of asparaginyl peptide ligases - Xia, Yiyin (2022)
Peptidyl asparaginyl ligases (PALs) are powerful tools for peptide macrocyclization. Herein, we report that a derivative of Asn, namely Nγ -hydroxyasparagine or Asn(OH), is an unnatural P1 substrate of PALs. By Asn(OH)-mediated cyclization, we prepared cyclic peptides as new matrix metalloproteinase 2 (MMP2) inhibitors displaying the hydroxamic acid moiety of Asn(OH) as the key pharmacophore. The most potent cyclic peptide (Ki =2.8±0.5 nM) was built on the hyperstable tetracyclic scaffold of rhesus theta defensin-1. The Asn(OH) residue in the cyclized peptides can also be readily oxidized to Asp. By this approach, we synthesized several bioactive Asp-containing cyclic peptides (MCoTI-II, kB2, SFTI, and integrin-targeting RGD peptides) that are otherwise difficult targets for PAL-catalyzed cyclization owing to unfavorable kinetics of the P1-Asp substrates. This study demonstrates that substrate engineering is a useful strategy to expand the application of PAL ligation in the synthesis of therapeutic cyclic peptides.